Cardio pulmonary resuscitation decisions in the emergency department: an ethnography of tacit knowledge in practice - Brummell, Steve; Seymour, Jane; Higginbottom, Gina M.A. (Elsevier, 2016)
Despite media images to the contrary, cardiopulmonary resuscitation in emergency departments is often unsuccessful. The purpose of this ethnographic study was to explore how health care professionals working in two emergency departments in the UK, make decisions to commence, continue or stop resuscitation. Data collection involved participant observation of resuscitation attempts and in-depth interviews with nurses, medical staff and paramedics who had taken part in the attempts. Detailed case examples were constructed for comparative analysis. Findings show that emergency department staff use experience and acquired tacit knowledge to construct a typology of cardiac arrest categories that help them navigate decision making. Categorisation is based on 'less is more' heuristics which combine explicit and tacit knowledge to facilitate rapid decisions. Staff then work as a team to rapidly assimilate and interpret information drawn from observations of the patient's body and from technical, biomedical monitoring data. The meaning of technical data is negotiated during staff interaction. This analysis was informed by a theory of 'bodily' and 'technical' trajectory alignment that was first developed from an ethnography of death and dying in intensive care units. The categorisation of cardiac arrest situations and trajectory alignment are the means by which staff achieve consensus decisions and determine the point at which an attempt should be withdrawn. This enables them to construct an acceptable death in highly challenging circumstances.